La Testimonianza di Giovanni Battista (Giov 1,19–28) come paradigma della Martyria della Chiesa - Senda, Siprianus Soleman; Taninas, Gaudensius; Abatan, Yofince (Pastoralia, 2025)
The Church carries out its mission through five fundamental dimensions: koinonia (communion), diakonia (service), liturgia (worship), kerygma (proclamation), and martyria (witness). Among these, martyria occupies a central role as the witness of faith in Christ in the world. This article aims to analyze the theological meaning of the testimony of John the Baptist in John 1:19–28 and its relevance as a paradigm of the Church’s martyria in the contemporary context. The study employs a qualitative method based on a literature review, using a biblical-theological analytical approach to the text of the Gospel of John. The findings indicate that John’s testimony is characterized by an authentic confession of faith, Christological humility, and a total orientation toward Christ as the center of proclamation. These characteristics affirm that the Church’s martyria is not self-centered but focused on the presence of Christ, made visible through a lived witness and authentic proclamation within the context of the contemporary world. Therefore, the testimony of John can serve as a model for the Church in carrying out its mission of martyria today.